Defence styles in a sample of forensic patients with personality disorder. (21st July 2014) - Huband, Nick; Duggan, Conor; McCarthy, Lucy; Mason, Lauren; Rathbone, Gillian
ABSTRACT Background Ego defences, often considered central to clinical work, have received surprisingly little attention in the forensic literature. Method In this exploratory study, 114 male inpatients completed the Defence Style Questionnaire (DSQ) following their admission to a specialist personality disorder (PD) service. Change in DSQ scores over time was examined using mixed effects models for those (n = 48) remaining in treatment for at least 18 months. Results Defensive functioning at baseline was less mature in comparison with non‐clinical norms, with two other non‐forensic PD samples, and with a male paedophile sample, but was unrelated to criminal history. Axis II severity was negatively associated with overall defensive functioning (ODF). Antisocial PD was positively associated with a maladaptive defence style. Borderline PD was negatively associated with self‐sacrificing defences. Avoidant PD was negatively associated with both self‐sacrificing and adaptive styles. Non‐completion of treatment was predicted by low ODF scores and high maladaptive defence style scores at baseline. ODF improved significantly over time in treatment and was predicted by strong antisocial and weak schizotypal PD pathologies. Conclusions Defence style, as measured by the DSQ, appears to have the potential to inform assessment and measure change in this group of offenders. Copyright © 2014 John Wiley & Sons, Ltd.